Cryptochrome 1 and phytochrome B control shade-avoidance responses in Arabidopsis via partially independent hormonal cascades - Keller, Mercedes M (Blackwell Publishing Ltd, 2011)
Plants respond to a reduction in the red/far-red ratio (R:FR) of light, caused by the proximity of other plants, by initiating morphological changes that improve light capture. In Arabidopsis, this response (shade avoidance syndrome, SAS) is controlled by phytochromes (particularly phyB), and is dependent on the TAA1 pathway of auxin biosynthesis. However, when grown in real canopies, we found that phyB mutants and mutants deficient in TAAI (sav3) still display robust SAS responses to increased planting density and leaf shading. The SAS morphology (leaf hyponasty and reduced lamina/petiole ratio) could be phenocopied by exposing plants to blue light attenuation. These responses to blue light attenuation required the UV-A/blue light photoreceptor cry1. Moreover, they were mediated through mechanisms that showed only limited overlap with the pathways recruited by phyB inactivation. In particular, pathways for polar auxin transport, auxin biosynthesis and gibberellin signaling that are involved in SAS responses to low R:FR were not required for the SAS responses to blue light depletion. By contrast, the brassinosteroid response appeared to be required for the full expression of the SAS phenotype under low blue light. The phyB and cry1 inactivation pathways appeared to converge in their requirement for the basic/helix-loop-helix (bHLH) transcription factors PHYTOCHROME INTERACTING FACTORs 4 and 5 (PIF4 and PIF5) to elicit the SAS phenotype. Our results suggest that blue light is an important control of SAS responses, and that PIF4 and PIF5 are critical hubs for a diverse array of signaling routes that control plant architecture in canopies.